The Commodification of Media Workers in the Television Entertainment Industry (Oratio Directa, 2018)
The commodification of workers in today’s television entertainment industry drives both production and distribution activities. Media institutions optimize workers’ labor and ideas by constructing the appeal of employment in the mass media industry, even when the wages received are inadequate. Commodification in the media concerns three interrelated elements: media content, audiences and advertising, and media workers. Consequently, media practitioners utilize public figures to attract audiences. This study examines Ananda Omesh as a media worker commodified by mass media to maintain the existence of the television program Family 100.
Keywords: Commodity; Mass media; Wage; Family 100; Media workers